Prevalence and Correlates of Sext-Sharing Among a Representative Sample of Youth in the Netherlands - Boer, Sarah; Erdem, Özcan; de Graaf, Hanneke; Götz, Hannelore (Frontiers in Psychology, 2021)
Many adolescents use their electronic devices to send each other sexually explicit texts, photos, and videos of themselves – commonly known as sexting. This can be fun and is not usually problematic. However, if the intended recipient decides to share these sexts with a broader audience, the consequences for the depicted can be detrimental. The purpose of this study was to investigate the prevalence of (non-consensual) sext-sharing among Dutch adolescents and explore the characteristics of those who do, to gain a better understanding of factors involved in dissemination. We used data from ‘Sex under the age of 25’, a representative national survey on sexual health among a sample of 20,834 Dutch 12-24-year-olds. The prevalence of sext-sharing was estimated using Complex Samples. Logistic regressions were used to assess associations between demographics, school-based sexting education, sexual- and online behavior, and mental health and sext-sharing. About 4% of the adolescents reported having shared someone else’s sext in the last six months. Being male, aged 12-14 years, frequent social media usage, watching online porn, sexual experience, and being subjected to sext-sharing themselves associated most strongly with sext-sharing. Our findings show that the likelihood of sext-sharing is lower in older adolescents and that it associates with the extent of adolescents’ sexual curiosity and online activity. The overlap between sharing sexts of others and having one’s own sext shared suggests that dissemination of personal sexual content might be normalized or used as an act of retribution. Further research could be helpful to explain the mechanisms underlying this overlap. The results of this study illustrate the importance of exposing adolescents to evidence based preventive educational interventions on sexting from 12 years onwards and not just within the context of traditional school-based sex education, but also as a part of the (online) media-literacy curriculum.